1995
DOI: 10.1002/art.1780380317
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class ii gene associations with anti–u1 small nuclear ribonucleoprotein antibody relationship to immunoreactivity with individual constituent proteins

Abstract: Objective. To better define immunogenetic associations with the anti–U1 ribonucleoprotein (U1 RNP) autoantibody response. Methods. HLA class II alleles were determined by genotyping in 49 Japanese rheumatic disease patients with anti–U1 RNP antibody and 43 race‐matched healthy controls. Immunoreactivities to U1 RNP constituent proteins (70K, A, B/B′, and C) were detected by immunoblots using purified HeLa cell Sm antigen, and antibody titer was determined by passive hemagglutination assay. Results. DQB1*0302 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
1
8
1
Order By: Relevance
“…In the Japanese population in particular, a significant genetic linkage between HLA DQB1 *0302 and anti-RNP has been shown to exist. 8 Miyagawa et al 9 reported that the haplotype DRB1 *08032 / DQA1 *0103 / DQB1 *0601 exhibited associations with anti-SS-B (with anti-SS-A together), and in their study, all the Japanese patients who were positive for anti-SS-A possessed at least one DQB1 *06 or *03 subtypes that shared the same amino acid residues at positions 71-77 of the DQB1 chain. Pt-1 and Pt-3 were positive for anti-dsDNA and lupus nephritis (nephrotic syndrome).…”
Section: Discussionmentioning
confidence: 96%
“…In the Japanese population in particular, a significant genetic linkage between HLA DQB1 *0302 and anti-RNP has been shown to exist. 8 Miyagawa et al 9 reported that the haplotype DRB1 *08032 / DQA1 *0103 / DQB1 *0601 exhibited associations with anti-SS-B (with anti-SS-A together), and in their study, all the Japanese patients who were positive for anti-SS-A possessed at least one DQB1 *06 or *03 subtypes that shared the same amino acid residues at positions 71-77 of the DQB1 chain. Pt-1 and Pt-3 were positive for anti-dsDNA and lupus nephritis (nephrotic syndrome).…”
Section: Discussionmentioning
confidence: 96%
“…'8 The numbers of alleles defined by this method are 44 (DRB1), 13 19). When an association with a particular specificity had been reported previously, the p value was not corrected."…”
Section: Hla Class II Altlel Typingmentioning
confidence: 99%
“…It has also been demonstrated that levels of autoantibodies to snRNP polypeptides are independently regulated [9,32]. Moreover, no disease-specific difference in HLA class II gene control of the anti-(U1)RNP autoantibody response has been demonstrated for either anti-70-kD or anti-C reactivities, and has also been hypothesized for anti-A and anti-B/B' reactivities [13].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, controversy still exists as to whether positivity to the 70-kD polypeptide alone or concurrently to the three U1 snRNP specific polypeptides is specific for MCTD [5,[8][9][10][11]. Moreover, it has been suggested that immunoreactivities to individual U1 snRNP constituent proteins are not disease-specific and are controlled by distinct HLA class II genes [12,13].…”
Section: Introductionmentioning
confidence: 99%